2015
DOI: 10.1177/1076029615575072
|View full text |Cite
|
Sign up to set email alerts
|

Recent Change in Treatment of Disseminated Intravascular Coagulation in Japan

Abstract: This study investigated the time trends and hospital factors affecting the use of drugs for infectious disease-associated disseminated intravascular coagulation (DIC) based on a national administrative database. A total of 14 324 patients with infectious disease-associated DIC were referred to 1041 hospitals from 2010 to 2012 in Japan. Patients' data were collected from the administrative database to determine time trends and hospital factors affecting the use of drugs for DIC. Three study periods were establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Recombinant human soluble thrombomodulin (rhTM), like AT, is frequently used as an anticoagulant for treating DIC 18, 23. Thrombomodulin is a receptor of thrombin and protein C on the endothelial cell surface and plays an important role in the regulation of coagulation and the innate immune system 24.…”
Section: Recombinant Human Soluble Thrombomodulinmentioning
confidence: 99%
“…Recombinant human soluble thrombomodulin (rhTM), like AT, is frequently used as an anticoagulant for treating DIC 18, 23. Thrombomodulin is a receptor of thrombin and protein C on the endothelial cell surface and plays an important role in the regulation of coagulation and the innate immune system 24.…”
Section: Recombinant Human Soluble Thrombomodulinmentioning
confidence: 99%
“… 4 Based on the national administrative database in Japan, Murata et al also reported the use of drugs for sepsis-induced DIC from 2010 to 2012. 11 In both of these studies, antithrombin (AT) and recombinant human soluble thrombomodulin (rhTM) were frequently used for the treatment of sepsis-induced DIC in Japan ( Table 1 ). However, the frequencies of heparin treatment differed greatly between the two studies.…”
Section: Drugs Available and Used For The Treatment Of Dic In Japan Amentioning
confidence: 99%
“…However, the frequencies of heparin treatment differed greatly between the two studies. 4 , 11 Although the indications for heparin treatment were unclear for patients with sepsis-induced DIC in the study by Murata et al, 11 they were specified in the Japan-Septic DIC study. 4 In the report by Murata et al, heparin treatment was not administered solely for the treatment of sepsis-induced DIC.…”
Section: Drugs Available and Used For The Treatment Of Dic In Japan Amentioning
confidence: 99%
See 1 more Smart Citation
“…Anticoagulant therapy for sepsis-associated disseminated intravascular coagulation (DIC) is widely performed in Japan [ 1 ], and antithrombin concentrate and recombinant thrombomodulin are the two most popular agents utilized for this treatment [ 2 ]. However, not a single anticoagulant has proven to be effective.…”
Section: Introductionmentioning
confidence: 99%